Development and Feasibility Testing of a Desktop-Based Learning Management System (LMS) Application Using the ADDIE Model - Nofrendy Azin; Nuur Wachid Abdul Majid; Rhezwan Dhaifullah Romdhoni (Journal of Informatics and Vocational Education, 2026)
Web-based Learning Management System (LMS) platforms face persistent limitations in Indonesia, particularly complete dependence on internet connectivity, which disrupts learning continuity for students in areas with inadequate digital infrastructure. This study aimed to develop and test the feasibility of a desktop-based LMS application, named EduDesk LMS, using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The application was built using the Tauri framework with Rust as the backend and React for the frontend, integrated with Supabase as the cloud database and authentication service. A key feature was an offline-online dual-mode mechanism, which allowed data to be stored locally when connectivity was unavailable and synchronized to the cloud automatically upon reconnection. The research subjects consisted of two educational technology experts for validation and 50 students selected through purposive sampling for the user trial. Data were collected using a Likert-scale questionnaire covering five assessment aspects: Display and Design, Ease of Use, Offline Feature, Usefulness, and User Satisfaction. Results showed that EduDesk LMS achieved a grand mean of 4.00, placing it in the Feasible category (3.41–4.20) across all five dimensions. The Display and Design aspect obtained the highest mean (4.09), followed by Usefulness (4.04), Ease of Use (4.03), User Satisfaction (3.94), and the Offline Feature (3.90). All aspects exceeded the minimum feasibility threshold of 3.41. These findings demonstrated that the ADDIE model effectively guided the development of a systematic, user-centered desktop LMS, and that EduDesk LMS constitutes a feasible platform for supporting flexible learning in higher education environments with varying connectivity conditions.